2021
DOI: 10.1177/02601060211054662
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of blended diet for enteral tube feeding in paediatrics: A case report

Abstract: Background: Advances in medical technology have resulted in changes to enteral tube feeding (ETF). Standard practice in the UK is to use commercial formula for ETF via the stomach or small intestine; however, blended diets are becoming increasingly popular. Emerging evidence shows benefits of a blended diet although evidence informing clinical guidance is sparse. Consequently, there is disparity in practice, and it remains unclear which patient groups may benefit most from a blended diet. Aim: To demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Papers included 12 narrative literature reviews (Bakewell et al, 2021; Bennett et al, 2020; Bobo, 2016; Carter et al, 2018; Chandrasekar et al, 2021; Elfadil et al, 2021; Fessler, 2015; Jeffery et al, 2022; Johnson et al, 2013; Martin & Gardner, 2017; Oparaji et al, 2019; Zettle, 2016), one systematic review (Bahramian et al, 2021), one integrative review (Schmitz et al, 2022), two scoping reviews (Breaks et al, 2018; Brekke et al, 2022), seven retrospective chart reviews (Alabbas & Dumant, 2022; Batsis et al, 2020; Kernizan et al, 2020; O'Flaherty et al, 2011; Pentiuk et al, 2011; Poole et al, 2021; Samela et al, 2017), five thesis (Bills, 2015; Breaks, 2019; Bronston, 2016; Durnan, 2018; Schoenfeld, 2013), seven case studies (Brown, 2014; Dipasquale et al, 2022; Gallagher et al, 2018; Khan et al, 2020; Phillips, 2022; Siddiqui et al, 2021; Thomas, 2017), three clinical guidelines (Bremner & Brooks, 2022; Escuro, 2014; Weeks, 2019), one opinion piece (Brown, 2015a), four conference abstracts (Brown, 2015b, 2018; Coles & Gallimore, 2021; Quigley & O'Sullivan, 2017), one rapid review (Coad et al, 2017), three qualitative studies (Durnan et al, 2019; Phillips, 2019; Soscia et al, 2021), nine quantitative survey designs (Armstrong et al, 2017; Boston & Wile, 2020; Epp, 2018; Epp et al, 2017; Johnson et al, 2015, 2018; Kariya et al,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers included 12 narrative literature reviews (Bakewell et al, 2021; Bennett et al, 2020; Bobo, 2016; Carter et al, 2018; Chandrasekar et al, 2021; Elfadil et al, 2021; Fessler, 2015; Jeffery et al, 2022; Johnson et al, 2013; Martin & Gardner, 2017; Oparaji et al, 2019; Zettle, 2016), one systematic review (Bahramian et al, 2021), one integrative review (Schmitz et al, 2022), two scoping reviews (Breaks et al, 2018; Brekke et al, 2022), seven retrospective chart reviews (Alabbas & Dumant, 2022; Batsis et al, 2020; Kernizan et al, 2020; O'Flaherty et al, 2011; Pentiuk et al, 2011; Poole et al, 2021; Samela et al, 2017), five thesis (Bills, 2015; Breaks, 2019; Bronston, 2016; Durnan, 2018; Schoenfeld, 2013), seven case studies (Brown, 2014; Dipasquale et al, 2022; Gallagher et al, 2018; Khan et al, 2020; Phillips, 2022; Siddiqui et al, 2021; Thomas, 2017), three clinical guidelines (Bremner & Brooks, 2022; Escuro, 2014; Weeks, 2019), one opinion piece (Brown, 2015a), four conference abstracts (Brown, 2015b, 2018; Coles & Gallimore, 2021; Quigley & O'Sullivan, 2017), one rapid review (Coad et al, 2017), three qualitative studies (Durnan et al, 2019; Phillips, 2019; Soscia et al, 2021), nine quantitative survey designs (Armstrong et al, 2017; Boston & Wile, 2020; Epp, 2018; Epp et al, 2017; Johnson et al, 2015, 2018; Kariya et al,…”
Section: Resultsmentioning
confidence: 99%
“…Five papers stressed that improvements in feeding and volume tolerance were highlighted in addition to a decreased aversion to feeding (Dipasquale et al, 2022;Durnan, 2018;Johnson et al, 2013;O'Flaherty et al, 2011;O'Sullivan et al, 2019). These included the reduction in physical symptoms of reflux and vomiting, improvement in anthropometric measures indicated by a visible improvement in appearance, with weight gain also noted in six papers (Carter et al, 2018;Jeffery et al, 2022;Phillips, 2019Phillips, , 2022Poole et al, 2021;Schmitz et al, 2022). One paper indicated that noticed improvement in the condition of child's skin, bowel regularity and alertness was evident (Fessler, 2015).…”
Section: Physical Well-beingmentioning
confidence: 99%
“…Blended diets (BDs) are an emerging and increasingly popular alternative that refers to regimens that utilize real, often homemade, foods blended to a smooth consistency 1 . An increasing amount of evidence has noted that patients on BDs have improved tolerance of their diets with decreases in retching, oral aversion, constipation, and reflux along with improved sleep, alertness, and mood 2–4 . There are also potential psychosocial benefits with improved bonding with caregivers and integration with family routines 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1 An increasing amount of evidence has noted that patients on BDs have improved tolerance of their diets with decreases in retching, oral aversion, constipation, and reflux along with improved sleep, alertness, and mood. [2][3][4] There are also potential psychosocial benefits with improved bonding with caregivers and integration with family routines. 4 Further, there is data suggesting children have decreased emergency department visits and hospital admissions, as well as overall improved quality of life.…”
Section: Introductionmentioning
confidence: 99%